E-LITIGATION AND HUMAN RIGHTS PROTECTION: ASSESSING EQUALITY BEFORE THE LAW AND PRIVACY RIGHTS AT THE TANJUNG PINANG ADMINISTRATIVE COURT - Rio Sandra Guari; Ampuan Situmeang; Hari Sutra Disemadi (Fakultas Hukum Universitas Kristen Indonesia, 2026)
Despite the rapid expansion of electronic court systems in Indonesia, scholarly discussions have largely emphasized procedural efficiency and administrative outcomes, leaving a critical gap in assessing E-Litigation as an instrument for the fulfillment of human rights. In particular, there remains limited empirical analysis on how the implementation of E-Litigation affects the principles of equality before the law and the protection of privacy rights, especially within administrative courts serving archipelagic regions. This research aims to analyze the effectiveness of E-Litigation implementation at PTUN Tanjung Pinang in fulfilling human rights—specifically equality before the law and privacy rights—through a comprehensive effectiveness assessment. The study employs an empirical juridical research method, combining statutory and conceptual analysis with qualitative field data obtained through interviews, observations, and document review, interpreted using Soerjono Soekanto’s theory of legal effectiveness. The findings demonstrate that E-Litigation at PTUN Tanjung Pinang is normatively effective due to a clear, firm, and adaptive regulatory framework that legitimizes electronic judicial processes. However, empirical effectiveness remains partial. Among the five effectiveness factors, only the legal factor operates effectively, while law enforcement capacity, facilities and infrastructure, societal readiness, and legal culture continue to face significant challenges. Uneven digital literacy, unstable internet connectivity, limited technological transparency, and transitional legal culture create practical barriers that disproportionately affect certain groups, particularly users in remote island areas. These conditions undermine equal access to justice and raise concerns regarding the protection of personal data in electronic proceedings. Overall, the study concludes that E-Litigation at PTUN Tanjung Pinang has not yet fully functioned as a comprehensive human rights protection mechanism. Strengthening human resources, improving infrastructure, enhancing public digital literacy, and fostering an adaptive legal culture are essential to ensure that judicial digitalization advances not only efficiency, but also substantive justice and human rights protection.